A crise da construção civil sob múltiplos pontos de vista: (des)regulação da atividade económica e recomposição do trabalho na perspetiva dos atores institucionais do setor da construção civil no período posterior a 2008 - Queirós, João; Galhano, Laura; Pereira, Virgílio Borges (Sociologia: Revista da Faculdade de Letras da Universidade do Porto, 2020)
This article presents the results of a sociological research dedicated to the understanding of the regulation of economic activity in the construction sector in Portugal. Combining a significant legislative inventory work with the identification of relevant institutional actors in the structuring of the activity in the sector under analysis, the article analyses, using elements obtained through semidirective interviews and “focus groups”, the positions taken by the referred actors. In addition to assessing the position of these actors on the evolution of the existing legal-normative framework, the focus is on the preparation of a sociological analysis of the demands arising from the economic crisis experienced in the construction sector in the period after 2008 and the study of the modalities of response to the crisis conveyed by the interviewees, considering, among others, aspects related to the organisation of work, inter-business relations, working and wage conditions and challenges associated with the technical and technological transformation taking place in the sector